Dostoievski: Filósofo de las pasiones humanas - Gueorguieva Gueorguieva, Margarita (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The principle of the literary work is the life. I document of the matter, comment of the immediate vivencia taken to its purest and deep meditation, forces that it overcomes the reality of the nature. The man's existential problems, of their being and to be in the world is the topic universal of the art: biography of the society. Being the literature, testimony of the culture, a form of the knowledge, we consider important to outline in this work some aspects that facilitate the study literary from the philosophical perspective, a new study of the narrative whose results us they will take to a current understanding of the work novelistic. One of the cardinal objectives for us is to reach a satisfactory conclusion: how the philosophical categories that propose an understanding of the knowledge of the destination and the man's existence, of the contents of the civilization and the culture, they are capable for one recreation of the literature. We want to show that studied the literary work from another angle (the proposal of a philosophy of Eugenio's Selections limit) and applying the aesthetics Theory hermeneutics, is possible to penetrate in the literary world that border among what can to be expressed and what you can conceptualize, to end up understanding, through the poetic one of the language, philosophical categories that become a poetic one philosophical.

El principio de la obra literaria es la vida – documento de la materia, comentario de la vivencia inmediata llevado a su más pura y honda meditación, fuerza que supera la realidad de la naturaleza. Los problemas existenciales del hombre, de su ser y estar en el mundo es el tema universal del arte: biografía de la sociedad. Siendo la literatura, testimonio de la cultura, una forma del conocimiento, consideramos importante plantear en este trabajo unos aspectos que posibiliten el estudio literario desde la perspectiva filosófica, un estudio nuevo de la narrativa, cuyos resultados nos llevarán a una actual comprensión de la obra novelística. Uno de los objetivos cardinales para nosotros es llegar a una conclusión satisfactoria: cómo las categorías filosóficas que proponen una comprensión del conocimiento del destino y la existencia del hombre, de los contenidos de la civilización y la cultura, son aptos para una recreación de la literatura. Queremos mostrar, que estudiada la obra literaria desde otro ángulo (la propuesta de una filosofía del límite de Eugenio Trías) y poniendo en práctica la Teoría de la estética hermenéutica, es posible penetrar en el mundo literario que fronteriza entre lo que puede expresarse y lo que se puede conceptualizar, para llegar a comprender, a través de la poética del lenguaje, categorías filosóficas, que devienen una poética filosófica.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2009-0023; Literaturas; Poesía; Limite; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/54